Exploring the relationship between social capital and hedonic well-being in sport and physical activity contexts: a scoping review - Yi Zhang; Keita Kinoshita; Shintaro Sato (Frontiers in Psychology)
This scoping review aimed to summarize the conceptualization and measurements of both social capital and hedonic well-being and to explore the links between social capital and hedonic well-being within sports and physical activity contexts. Articles were sourced from five databases, including PubMed, Scopus (Elsevier), SPORTDiscus, Web of Science, and Google Scholar. Initially, 475 papers were identified. After applying the screening process, 24 papers were included. The majority (70.8%) indicated a positive relationship between social capital and hedonic well-being, while others found no direct connection (16.7%) or presented mixed results (12.5%). The review underscored a consensus on defining and measuring hedonic well-being, but it also revealed the need for a more refined conceptualization and universally accepted measurement of social capital within sports research. The findings highlighted the positive associations between social capital and hedonic well-being in sport and physical activity contexts, suggesting future research directions including an examination of potential downsides.